The savings-inflation puzzle - Burkhard Heer; Bernd Süssmuth (Center for Economic Studies and ifo Institute (CESifo), 2006)
We find that inflation did not unanimously decrease savings in the US during the postwar period. This result is puzzling as it contradicts the implications of most monetary general equilibrium models.
Keywords: E65; E21; 330; inflation; savings; nominal interest taxation; Sparen; Inflation; Schätzung; USA